Multiparametric vs. Inferior Vena Cava–Based Estimation of Right Atrial Pressure - Toma, Matteo; Giovinazzo, Stefano; Crimi, Gabriele; Masoero, Giovanni; Balbi, Manrico; Montecucco, Fabrizio; Canepa, Marco; Porto, Italo; Ameri, Pietro (Frontiers in Cardiovascular Medicine, 2021)
Background: Right atrial pressure (RAP) can be estimated by echocardiography from inferior vena cava diameter and collapsibility (eRAPIVC), tricuspid E/e′ ratio (eRAPE/e′), or hepatic vein flow (eRAPHV). The mean of these estimates (eRAPmean) might be more accurate than single assessments. Methods and Results: eRAPIVC, eRAPE/e′, eRAPHV (categorized in 5, 10, 15, or 20 mmHg), eRAPmean (continuous values) and invasive RAP (iRAP) were obtained in 43 consecutive patients undergoing right heart catheterization [median age 69 (58–75) years, 49% males]. There was a positive correlation between eRAPmean and iRAP (Spearman test r = 0.66, P < 0.001), with Bland–Altman test showing the best agreement for values <10 mmHg. There was also a trend for decreased concordance between eRAPIVC, eRAPE/e′, eRAPHV, and iRAP across the 5- to 20-mmHg categories, and iRAP was significantly different from eRAPE/e′ and eRAPHV for the 20-mmHg category (Wilcoxon signed-rank test P = 0.02 and P < 0.001, respectively). The areas under the curve in predicting iRAP were nonsignificantly better for eRAPmean than for eRAPIVC at both 5-mmHg [0.64, 95% confidence interval (CI) 0.49–0.80 vs. 0.70, 95% CI 0.53–0.87; Wald test P = 0.41] and 10-mmHg (0.76, 95% CI 0.60–0.92 vs. 0.81, 95% CI 0.67–0.96; P = 0.43) thresholds. Conclusions: Our data suggest that multiparametric eRAPmean does not provide advantage over eRAPIVC, despite being more complex and time-consuming.